Osteoporosis: prevention and management. (2nd March 2023) - Walker, Jennie
Abstract : Osteoporosis is a common skeletal condition that is characterised by low bone mass, increased bone fragility and an increased risk of fracture. It is important to understand who may be at risk of developing osteoporosis and sustaining fragility fractures so that appropriate steps can be taken to minimise any modifiable risk factors. Simple lifestyle changes, such as increasing physical activity, stopping smoking and ensuring adequate nutritional intake, can improve musculoskeletal health and reduce fracture risk.